Understanding on islamic inheritance among students bachelor of muamalat UiTM Shah Alam / Nurul Ilya Aqilah Mohd Rozali - Mohd Rozali, Nurul Ilya Aqilah (2019)
This study aimed to identify the understanding on Islamic inheritance among students Bachelor of Muamalat UiTM, Shah Alam. 75 students were selected to be the respondent in this research. The researcher using the method descriptive analysis in determine the result. This study chose the quantitative research methodology in which a set of questionnaires which consists of 23 items that were divided into 5 different sections was used as the research instrument. The objectives in this study, firstly, to identify the level of understanding on Islamic Inheritance among students Bachelor of Muamalat UiTM Shah Alam. Secondly, to examine student's perceptions regarding the importance of Islamic Inheritance in life. Lastly, to analyse the differences level between understanding and students' perception on Islamic Inheritance among student Bachelor of Muamalat UiTM based on gender. The researcher found that the mean level of understanding on Islamic Inheritance among students' is at a high level of 4.15 and mean for the students' perception regarding the important of Islamic Inheritance in their life is also at high level of 4.57. But for the practice of Islamic Inheritance the finding indicates that majority of respondents still lack of understanding.